2018
DOI: 10.1021/acs.jchemed.8b00431
|View full text |Cite
|
Sign up to set email alerts
|

Simple Acid Vapor Method for Production of HCl and DCl Gas for IR Spectroscopy

Abstract: We report here a method that utilizes the vapor pressure of HCl(g) above a concentrated HCl(aq) solution as an extremely simple and safe method to produce small amounts of HCl vapor in an IR gas cell. This vapor pressure approach can also be used to produce DCl(g) by introducing a few drops of concentrated DCl(aq) into the gas cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Therefore, there are reasonable reasons to believe that the Co-NPs@NC-T can directly capture NH 3 from the AP surface, eliminating the SD process by weakening the accumulation of NH 3 on the AP surface, and exhibiting excellent catalytic activity. In addition, the binding energies of NH 2 , NH, and N species for all planes show a gradually decreasing trend (Figure S10 and Figure S11), which indicates the clear trend of dissociation of NH 3 , and then the NH 3 dissociated species, proton, and NC react with the adsorbed oxidizing species by Co-NPs 69,70 to generate N 2 O (2180-2260 cm -1 and 1250-1330 cm -1 ) 71 , NO (1750-1840 cm -1 ) 72 , NO 2 (1560-1650 cm -1 ) 72 , CO 2 (2350 cm -1 and 670 cm -1 ) 67 , H 2 O (3480-3625 cm -1 ), and HCl (2685-3025 cm -1 ) 73 (Figure 4b), while the the Co-NPs@NC-T gradually oxidizes and burns to release heat, which in turn promotes the AP thermocatalytic decomposition process (Figure 4c). Therefore, The Co-NPs@NC-T possess excellent catalytic activity in line with expectations.…”
Section: Catalytic Activity and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there are reasonable reasons to believe that the Co-NPs@NC-T can directly capture NH 3 from the AP surface, eliminating the SD process by weakening the accumulation of NH 3 on the AP surface, and exhibiting excellent catalytic activity. In addition, the binding energies of NH 2 , NH, and N species for all planes show a gradually decreasing trend (Figure S10 and Figure S11), which indicates the clear trend of dissociation of NH 3 , and then the NH 3 dissociated species, proton, and NC react with the adsorbed oxidizing species by Co-NPs 69,70 to generate N 2 O (2180-2260 cm -1 and 1250-1330 cm -1 ) 71 , NO (1750-1840 cm -1 ) 72 , NO 2 (1560-1650 cm -1 ) 72 , CO 2 (2350 cm -1 and 670 cm -1 ) 67 , H 2 O (3480-3625 cm -1 ), and HCl (2685-3025 cm -1 ) 73 (Figure 4b), while the the Co-NPs@NC-T gradually oxidizes and burns to release heat, which in turn promotes the AP thermocatalytic decomposition process (Figure 4c). Therefore, The Co-NPs@NC-T possess excellent catalytic activity in line with expectations.…”
Section: Catalytic Activity and Mechanismmentioning
confidence: 99%
“…In addition, the binding energies of NH 2 , NH, and N species for all planes show a gradually decreasing trend (Fig. S10 and S11, ESI †), which indicates the clear trend of dissociation of NH 3 , and then the NH 3 dissociated species, protons, and NC react with the adsorbed oxidizing species by Co-NPs 69,70 to generate N 2 O (2180-2260 cm À1 and 1250-1330 cm À1 ), 71 NO (1750-1840 cm À1 ), 72 NO 2 (1560-1650 cm À1 ), 72 CO 2 (2350 cm À1 and 670 cm À1 ), 67 H 2 O (3480-3625 cm À1 ), and HCl (2685-3025 cm À1 ) 73 (Fig. 4b), while the Co-NPs@NC-T gradually oxidize and burn to release heat, which in turn promotes the AP thermocatalytic decomposition process (Fig.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…HCl in such experiments can come directly from a gas cylinder or can be generated through a variety of chemical means. These include reactions of phosphorus trichloride with water, benzoyl chloride with water, and concentrated sulfuric acid with potassium chloride . It has also been shown that the vapor pressure of a concentrated HCl solution alone is enough to produce enough HCl in the gas phase to make the required spectroscopic measurement, , but all of these methods still require chemical reagents to be used in the sample preparation of gas phase HCl.…”
Section: Educational Advantages Of Carbon Dioxidementioning
confidence: 99%
“…The first example of a rotationally resolved HCl infrared (IR) spectrum in this Journal along with a discussion of the theory was from Stafford et al in 1963 . Since that time, papers have been published about different aspects of the HCl/DCl experiment including the following: increasing the resolution of the spectrum, using computer programs or spreadsheets to analyze the data, simulating the spectra, modeling potential curves, , and connecting it with statistical mechanics. , The HCl/DCl IR experiment is so prevalent that there are many journal articles devoted to describing safe and efficient techniques to generate HCl and DCl gas in the physical chemistry laboratory. …”
Section: Introductionmentioning
confidence: 99%